Organic pattern in painting in art education / Talfiza Taufik - Taufik, Talfiza (2010)
Of late, people are ignorant of organic pattern in painting in art education. A combination of color, surface and materials have been shown in this form of artwork.This research explored the use of organic and abstract images that are taken from nature and natural resources into the mixed media work. The research further explained about the process and production of an interesting and attraction piece of artwork in organic pattern. The focus of this study is to have a deep understanding in exploring organic pattern in painting in art education. The experimental research will shows how to produce an organic art piece in different way, style and techniques based on the model of art education theory. Based on the above studies and research, the researcher produces artwork reflecting the contents of studies as in this compilation.